Bayesian perspectives on the discovery of the Higgs particle. - Dawid, Richard (Synthese, 2017)
It is argued that the high degree of trust in the Higgs particle before its discovery raises the question of a Bayesian perspective on data analysis in high energy physics in an interesting way that differs from other suggestions regarding the deployment of Bayesian strategies in the field.